Assessing the risks of fintech development: the case of online illegal capital raising - Zhang, Xin; Shi, Jihong; Zhao, Jinsong; Wu, Xiuqin (Technological and Economic Development of Economy, 2025)
This study examines the impact of financial technology (FinTech) on online illegal capital raising (ICR) in China. Using a large dataset of court judgments from China Judgment Online from 2014 to 2019, we observe a steady increase in the number and proportion of defendants involved in online ICR cases. Our empirical analysis shows that FinTech contributes significantly to the increase in online ICR, particularly in regions with low opportunity costs of crime and limited access to traditional financial services. The findings remain robust to different FinTech proxies, sample adjustments, and considerations of potential endogeneity. Weak regulatory oversight and higher potential criminal returns are key channels through which FinTech promotes online ICR. These findings highlight the need for stronger financial regulation, especially in high-risk regions, alongside efforts to improve public awareness of online investment risks. Strengthening regulation while promoting the positive role of FinTech in financial development is critical to mitigating emerging financial risks.First published online 15 April 2025